ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN LIKUIDITAS PADA PT. ASTRA AGRO LESTARI, TBK - Stefany, Elista Dewi; Leiwakabessy, Pitter; Pangkerego,, Christian Valen (LPPM Politeknik Saint Paul Sorong, 2021)
The purpose of liquidity management is to maintain the company's or organization's ability to reduce liquidity risk. By managing the Company's liquidity, it will increase the trust of the Company's internal and external parties. As a public company, PT Astra Agro Lestari Tbk is required to be able to manage its working capital and maintain its liquidity level in order to avoid future liquidity problems and also to increase investor confidence. Working capital turnover ratio, current ratio, quick ratio, and cash ratio can be used to determine the level of liquidity in a business. In managing working capital, PT. Astra Agro Lestari Tbk's working capital management at PT is known from calculations and analysis for 2018–2020. Astra Agro Lestari Tbk is not working at the moment. This is due to low inventory turnover. regarding the liquidity ratio of PT. Astra Agro Lestari Tbk's liquidity as measured by the current ratio, quick ratio and cash ratio shows that the liquidity ratio as measured by the current ratio shows 3.3 times or